HUBUNGAN KEPADATAN LALAT DAN SANITASI PENGOLAHAN LIMBAH DENGAN KEJADIAN DIARE PADA MASYARAKAT PENGOLAH IKAN ASIN DI KELURAHAN HAJORAN KECAMATAN PANDAN KABUPATEN TAPANULI TENGAH TAHUN 2022 - DEVI KRISTINA HUTAGALUNG; TINAWATI NAINGGOLAN; PUTRI SIREGAR (LP2MTBM MAKARIOZ, 2023)
Diarrhea is a condition when a person with a frequency of defecation (defecation) more than 3 (three) times a day with a soft or liquid stool consistency and can even be liquid only. According to research data from the World Health Organization (WHO) in 2017, every year 525,000 cases of death in the community are caused by diarrheal disease. Diarrhea can be caused by contaminated food and drink through disease vectors. Flies are one of the mechanical vectors of various diseases because flies spread disease agents that come from various surfaces and contaminate the food and drinks they live on or only transfer bacteria that are on the surface of their bodies. This study aims to determine the relationship between fly density and waste treatment with the incidence of diarrhea in salted fish processing communities in Hajoran Village, Pandan District, Central Tapanuli Regency in 2022. This research is an observational analytic research with a cross-sectional study approach. The data collection method uses a questionnaire given to respondents who have met the inclusion criteria and measures the level of fly density using a fly grill. The sample collection method used a total population technique of 72 family heads. Based on the analysis conducted using the chi-square method, the results showed that there was a relationship between personal hygiene and the incidence of diarrhea with a value of p=0.042 (p<0.05), the relationship between basic sanitation and the incidence of diarrhea with a value of p=0.000 (p<0.05), and the relationship between the level of fly density and the incidence of diarrhea with a value of p=0.000 (p<0.05). Based on these results, there is a relationship between the level of fly density, personal hygiene, and basic sanitation with the incidence of diarrhea in the community.